Some Sacred Plants of Andaman and Nicobar Islands, India - Fouziya Saleem; R. B. Yadav; Lal Ji Singh (International Journal of Economic Plants)
The present paper describes the sacred plants and their medicinal uses in Andaman and Nicobar Islands based on intense surveys. A total of 42 sacred plant species are found in close vicinity of people of these Islands and somehow linked with God and goddess and are used in variety of ceremonies throughout the year by the various Communities.